Treatment of dermatophytosis and superficial fungal infections. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2001)
The treatment of dermatophytoses should be associated to the identification of the source of the infection. The latter can be helped by the identification of the responsible mycotic agent thanks to the mycological culture. A systemic treatment is indicated when the lesions affect more than 10% of the skin surface and are far each other, when areas close to terminal hairs are affected and finally in immunocompromised subjects. The topical treatment is based upon the new antimycotic agents, particularly imidazoles. In case of intense inflammation, a topical corticosteroid cream, possibly associated to an antimycotic agent, is initially indicated. The treatment of tinea corporis, tinea inguinalis with a mention to diaper rash, tinea pedis and finally pityriasis versicolor is discussed.